Challenges of Primary Healthare and stakes of health communication - Peñafiel-Saiz, Carmen; Ronco-López, Milagros (Revista Española de Comunicación en Salud, 2025)
Primary Care (PC) has a prominent role in public health because it includes the whole of society and aims to ensure the highest possible level of health and well-being. The Member States of the European Union are committed to renewing and expanding PC as the cornerstone of a sustainable health system to achieve Universal Health. Objectives. To show the values of PA as the main interface between the health system and individuals and the main current gaps. PA can shape and reshape health systems to make them more accessible, more integrated and more sustainable. . A qualitative-documentary methodology of a criticalinterpretative nature was used to analyze the texts produced by the Institutions and Organizations, chosen by means of a systematic selective sampling based on a deliberate and intentional selection criterion for their perceived importance in the field of PA. Conclusions. The efficiency offered by PA and its potential to achieve the Sustainable Development Goals is still struggling with insufficient resources and quality PA requires time, collaboration, specialized training and investment in professionals.
Keywords: Primary Care; communication and health; challenges of Primary Care; health information; health management; Sustainable Development Goals; public health